2021
DOI: 10.1108/qae-12-2020-0152
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and intrinsic motivation towards the online component of blended learning in accounting education: evidence from a Malaysian public university

Abstract: Purpose This study aims to explore the extrinsic and intrinsic motivational factors that affect accounting students’ acceptance behaviour towards the online component of blended learning (OCBL) in the context of COVID-19. Design/methodology/approach A sample of 354 accounting students from a Malaysian public university was selected. Confirmatory factor analysis, correlation and regression analysis and an independent sample t-test were used for data analysis. Findings The results showed that the predictor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Students' perception of the summative assessment of introduction to financial accounting in the first year gives positive feedback. This positive feedback includes the advantages of first-line assessment in learning, motivation, and engagement (Liu & Zainuddin, 2021;Ross et al, 2018). Next, another studies also argue a positive correlation between students' performance in an online assessment and their final exam score.…”
Section: Students Engagement In Online Learningmentioning
confidence: 93%
“…Students' perception of the summative assessment of introduction to financial accounting in the first year gives positive feedback. This positive feedback includes the advantages of first-line assessment in learning, motivation, and engagement (Liu & Zainuddin, 2021;Ross et al, 2018). Next, another studies also argue a positive correlation between students' performance in an online assessment and their final exam score.…”
Section: Students Engagement In Online Learningmentioning
confidence: 93%
“…Ramachandra and Wells (2021) found that students were severely challenged in sense-making with conceptual, application, and judgement-related issues and understanding of administrative requirements of an accounting conversion master's degree in New Zealand during the pandemic lockdown. Liu and Zainuddin (2021) studied the extrinsic and intrinsic motivational factors that affect accounting students' acceptance behaviour towards the online learning component of a blended learning course in Malaysia and found that the perceived value appeared to be the most influential factor while the perceived ease of use was not influential.…”
Section: Studies Related To Online Students' Perceptionsmentioning
confidence: 99%
“…In other words, the institution must be able to solve the real problems confronted by students and enhance their learning in quantity and quality [34]. They should provide sufficient guidance and training to improve students' skills, particularly in the COVID-19 era [35] [56]. Approximately, sudden changes in professional practices in the field of education have caused changes in the anxiety, depression, and stress levels of education workers and students [54].…”
Section: Cluster 3: Educationmentioning
confidence: 99%